A Comparator for the First and Second Editions of John Milton’s Paradise Lost - Cunningham, Richard (Renaissance and Reformation / Renaissance et Réforme, 2021)
In this article, Cunningham offers a non-programmer’s approach to building a means of examining the differences between the ten-book first edition of Paradise Lost and the subsequent twelve-book second edition. The Comparator referenced in the article title will form part of what, in effect, will be a new kind of online scholarly edition, one that facilitates student annotations of texts while also asking salient questions about how the commonplace tool of a web browser might help transform how we interact with texts. Cunningham’s workflow in building the Comparator suggests that this kind of successful and useful digital humanities work can be achieved with modest means and only a modest level of DH knowledge.